The Quality of Student Services Provided by the Deanship of Student Affairs at Sultan Qaboos University - Wajeha T. Al-Ani; Zahra N. Al-Rasbiya (Sultan Qaboos University, 2013)
This study aimed to investigate the quality of student services provided by the Deanship of Student Affairs at the Sultan Qaboos University. The study sample consisted of 610 students. Data were collected using a questionnaire consisting of 59 items distributed in seven areas which are: social services, housing services, and food services, and counseling and religious guidance services, cultural and artistic services, sports activities, and sustainable training services. The results showed that the highest mean of the responses is in the counseling and religious guidance 3.79, while the lowest mean is for the area of student food services 2.82.the Results of (MANOVA) showed that the quality of services provided by the Deanship of Student Affairs for students for female was a higher level compared with males in the areas of social services, housing services and sustainable training services. As for the results on the year variable, the result of the study revealed that there are statistically significant differences (α=0.05) related to the field of social services in favor of the second year students. Also the results showed that there are statistically significant differences related to students' points of view in humanities colleges in the areas of social services 3.37, and sustainable training 3.27, while in the area of religious guidance services it is in favor of scientific colleges 3.87. Based on the results of this study, many recommendations and suggestions were developed.